An Integrated Approach for Treating Discourse in Aphasia Bridging the Gap Between Language Impairment and Functional Communication. - Milman, Lisa (Topics in Language Disorders)
Purpose: A primary goal of aphasia intervention is to improve everyday communication. Although a large body of research focuses on treatment generalization, transfer of learning to real-world interactions involving discourse does not always occur. The goal of an integrated discourse treatment for aphasia (IOTA) approach is to facilitate such generalization. This article reviews generalization data from a series of four closely related IDTA studies. Method: Treatment in all studies (two case reports and two single subject experimental designs) followed a problem-based learning model targeting word retrieval, sentence processing, and discourse production. Results: Seven of eight participants acquired the target vocabulary and sentence structures. In addition, generalization was evident for most participants on related linguistic structures, standardized tests of language and cognition, and/or measures of spoken discourse production. Conclusions: Findings add to previous research supporting an IDTA approach to improving discourse in persons with aphasia. Participant characteristics and properties of outcome measures associated with these results are also discussed.